Public Opinion, the Media and the Principles of Ethics - Adam Lepa (Nicolaus Copernicus University in Toruń, 2011)
The article takes up the issue of the role of the media in shaping public opinion. The process involves the following mechanisms: whispered propaganda, opinion leadership, logomachy, the spiral of silence, political correctness and opinion polls. The media shape public opinion while they seek to accomplish their primary objectives: to inform, to entertain and to educate. Efforts to shape public opinion should allow for an ethical dimension and should be based on truth in relation to procedures involved in opinion polling, accuracy of information and dependability of data reporting.